2023
DOI: 10.3390/foods12112144
|View full text |Cite
|
Sign up to set email alerts
|

Meat Consumption, Sustainability and Alternatives: An Overview of Motives and Barriers

Abstract: Meat and meat products are important sources of protein in the human diet. However, their consumption or excessive consumption has been questioned as this has been related to sustainability and health issues. Due to this, alternatives to conventional meat consumption, such as meat produced more sustainably or meat alternatives, have been considered. The aim of the present work is to gain insight into the meat consumption of different countries, the motives for and barriers to this consumption, as well as into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 78 publications
2
12
0
3
Order By: Relevance
“…Troska o zwierzęta i dobrostan środowiska naturalnego to ważne czynniki, które przyciągają konsumentów do produktów roślinnych [Font-i-Furnols, 2023]. W związku z tym marki powinny w większym stopniu wykorzystywać te motywy w swojej komunikacji w mediach społecznościowych.…”
Section: Konkluzjeunclassified
See 2 more Smart Citations
“…Troska o zwierzęta i dobrostan środowiska naturalnego to ważne czynniki, które przyciągają konsumentów do produktów roślinnych [Font-i-Furnols, 2023]. W związku z tym marki powinny w większym stopniu wykorzystywać te motywy w swojej komunikacji w mediach społecznościowych.…”
Section: Konkluzjeunclassified
“…Wzrost popularności i sprzedaży RZM jest silnie związany z głównymi motywami ograniczania spożycia mięsa. Należą do nich przede wszystkim: troska o klimat i dobrostan środowiska naturalnego, poprawa stanu zdrowia oraz etyczne aspekty hodowli i uboju zwierząt [Van Loo, Caputo i Lusk, 2020;Font-I-Furnols, 2023]. Do głównych atutów RZM należą też ich cechy sensoryczne.…”
Section: Roślinne Zamienniki Mięsa Jako Korzyść Dla śRodowiska Ludzi ...unclassified
See 1 more Smart Citation
“…A high proportion of people in developed countries are currently consuming significantly more than this. Meanwhile, livestock farming contributed negatively to the environmental due to greenhouse gas (GHG) emissions, land and water use, acidification, and eutrophication [19]. Results of research indicated that animal products in the form of meat, aquaculture, eggs, and dairy use about 83% of the world's farmland and contribute about 57% of foods' different emissions, while providing only 37% of world protein and 18% of calories.…”
Section: Cultured Meat [11 -18]mentioning
confidence: 99%
“…Pork meat has gained significant prominence and emerged as a highly consumed meat in Asia and Europe [ 1 ] due to its high protein content and essential fatty acids, particularly saturated fatty acids, which are intricately linked to human health considerations [ 2 ]. Recently, there has been increasing interest in how to produce high-quality pork.…”
Section: Introductionmentioning
confidence: 99%